Mindfulness-Based Midwife Reproductive Health Education Approach - Husnul Khotimah Rustam; Kassaming; Nur Rahmatan Mursalin; Isakka Syam (Medikun Publisher, 2024)
This study aims to empower village midwives through reproductive health and mindfulness education to improve the professionalism of health workers. The method used is a participatory approach by involving village midwives in an intensive training program. This program includes materials on reproductive health, mindfulness techniques, and practical applications in health services. The results of the study showed that reproductive health and mindfulness education significantly improved the knowledge, skills, and professional attitudes of village midwives. In addition, this program also had a positive impact on the quality of health services provided to the community. In conclusion, empowering village midwives through reproductive health and mindfulness education is an effective strategy to improve the professionalism of health workers in rural areas.